Integration Halal Supply Chain, Sustainability, Environmental Ethics, and Maqashid Syariah in The Halal Industry - Hasanah, Hikmatul -; Devi Hardianti Rukmana; Mutmainnah; Moh. Ali Syaifudin Zuhri; Uke Cahya Ningrum; Mahfiyah (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
In the face of global dynamics and growing Muslim consumer awareness of halal products, as well as environmental concerns, the integration of the Halal Supply Chain, sustainability principles, ecological ethics, and Maqasid Syariah (the principles of Islamic law) is becoming increasingly important. The method used is a literature review, which examines research results to provide a comprehensive overview of the development and position of this research compared to existing research. This integration of concepts is intended to encourage macro policies related to the halal industry and will organize micro areas related to company or business actor practices. This article aims to illustrate the interrelationship of these concepts within a mutually supportive strategic framework, resulting in the formulation of an integrated model that not only meets halal standards but is also socially and environmentally responsible within the corridor of Islamic values. The implications can increase consumer trust, strengthen brand image, expand market access, and contribute to sustainable development.